Temporal and Spatial Variations of Tropospheric Ozone over the Arctic - Zhao, Yue Cheng (2019)
This study aims to address the temporal and spatial variations of tropospheric ozone over the Arctic from the 1980s to 2010s, using ozonesonde data and the Trajectory-mapped Ozonesonde dataset for the Stratosphere and Troposphere (TOST) data. In the lower and middle troposphere, ozone abundances are the highest over Europe and over the Atlantic between 60-70°, while in the upper troposphere, ozone peaks over the Canadian Arctic. Seasonally, the regional means of ozone abundances in the lower and middle troposphere usually are at maximum in spring. During the four decades, the ozone trends over the Arctic troposphere are generally positive, and the fastest increase took place in the 1990s. By season, the increasing trends are larger in winter and spring than in summer and fall. This study offers new understanding of the tropospheric ozone variations in the entire Arctic from perspectives of spatial variations, seasonal variations, and long-term trends. M.Sc.